PERANCANGAN SISTEM KEAMANAN BRANKAS DENGAN VERIFIKASI PASSWORD DAN SIDIK JARI BERBASIS IOT - Andi Aziz Mahligai; Nur Iksan; Pamor Gunoto; Ismail Yusuf Panessai (SIGMA TEKNIKA, 2022)
The safe box is one of the targets of theft crimes. With today's technological advances, the parts of our bodies can be used as unique identities so that they can be used as system access. This method is quite good because the security system can immediately recognize the physical characteristics of the owner when opening the safe. In this case the authors make a safe box security system with passwords and fingerprints verification based on IoT. This system uses a combination interlock where the fingerprint scanner cannot perform a fingerprint scan without entering a password. Then the alarm will sound, and the system will send a telegram message notification to the safe owner's cell phone if there is an error more than three times when entering the password or during fingerprint scanning, as well as when the safe door is open and when the safe lose of primary power supply to avoid the possibility of the safe moving when there is a theft. Keypad and fingerprint scanner to open the safe door. NodeMcu V3 as a medium for sending data from the microcontroller system to the safe owner's cell phone to provide information to the safe owner in the event of an attempt to break into the safe by someone else. LCD screen as a guide in the process of opening the safe door. From the manufacture of this tool, it is hoped that if someone who wants to break into a safe will be easily identified and maintain more security.